Nosná železobetonová konstrukce obchodního domu - Zdražilová, Pavlína (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Tato bakalářská práce se zabývá návrhem a posouzením vybrané části nosné železobetonové monolitické konstrukce obchodního domu. Cílem práce bylo navrhnout a posoudit železobetonovou konstrukci stropní desky nad prvním nadzemním podlažím a jednoho sloupu. K vytvoření modelu a získání vnitřních sil byl zvolen program Scia Engineer 14. Konstrukce je navržena podle norem ČSN EN.

This bachelor thesis deals with design and assessment of chosen parts of load-bearing reinforced concrete cast-in-place structure of a department store. The aim of this thesis is to design and assess the reinforced concrete structure of a slab above first floor and one column. Scia Engineer 14 computational software was chosen to model the structure and to obtain the international forces. The structure is designed according to ČSN EN.
Reinforced concrete structure
Keywords: Beton; výztuž; obchodní dům; lokálně podepřená deska; sloup; vnitřní síly; zatěžovací stavy; metoda součtových momentů; ohyb; protlačení; mezní stav únosnosti; mezní stav použitelnosti; Concrete; reinfrocement; department store; locally supported slab; column; internal forces; load cases; the method of summation moments; bending; punching; ultimate limit state; serviceability limit state